Odpowiedź :
Oblicz:
a) 5⁻⁵ * 4⁻⁷ * 0,05⁻⁷=5⁻⁵*4⁻⁷*(1/20)⁻⁷=5⁻⁵*4⁻⁷*((20)⁻¹)⁻⁷=5⁻⁵*4⁻⁷*((4*5)⁻¹)⁻⁷=5⁻⁵*4⁻⁷*(4*5)⁷=5⁻⁵*4⁻⁷*4⁷*5⁷=5²=5*5=25
b) [49⁻⁶ * 6⁶]/[7⁻¹²]=[(7²)⁻⁶*6⁶]/[7⁻¹²]=[7⁻¹²*6⁶]/[7⁻¹²]=6⁶=46656
c) ²√(2/9) : ²√(8/25)=√[(2/9):(8/25)]=√[(2/9)*(25/8)]=√(50/72)=√(25/36)=√25/√36=5/6
a) 5⁻⁵ * 4⁻⁷ * 0,05⁻⁷=5⁻⁵*4⁻⁷*(1/20)⁻⁷=5⁻⁵*4⁻⁷*((20)⁻¹)⁻⁷=5⁻⁵*4⁻⁷*((4*5)⁻¹)⁻⁷=5⁻⁵*4⁻⁷*(4*5)⁷=5⁻⁵*4⁻⁷*4⁷*5⁷=5²=5*5=25
b) [49⁻⁶ * 6⁶]/[7⁻¹²]=[(7²)⁻⁶*6⁶]/[7⁻¹²]=[7⁻¹²*6⁶]/[7⁻¹²]=6⁶=46656
c) ²√(2/9) : ²√(8/25)=√[(2/9):(8/25)]=√[(2/9)*(25/8)]=√(50/72)=√(25/36)=√25/√36=5/6
a) 5⁻⁵*4⁻⁷*0,05⁻⁷= 5⁻⁵ * ¼⁷* 20⁷ = 5⁻⁵ * 5⁷ = 5⁻⁵*5⁷ = 5² = 25
b) 49⁻⁶*6⁶/7⁻¹²= 7⁻¹² * 6⁶/7⁻¹² = 6⁶ = 36
c) √2/9 : √8/25 = √(2/9 : 8/25) = √(2/9*25/8) =√(25/36)= 5/6
b) 49⁻⁶*6⁶/7⁻¹²= 7⁻¹² * 6⁶/7⁻¹² = 6⁶ = 36
c) √2/9 : √8/25 = √(2/9 : 8/25) = √(2/9*25/8) =√(25/36)= 5/6